Pengaruh Yoga Anak Terhadap Kecerdasan Spiritual Anak Pra Sekolah di Desa Kebonromo Kecamatan Ngrampal Kabupaten Sragen - Bela Putri Karisma; Ninik Christiani (Journal of Holistics and Health Science, 2021)
Optimizing spiritual intelligence requires a long process and requires practice, the earlier the child is trained to develop spiritual intelligence, the greater the benefits include being able to recognize themselves, being able to recognize the strengths and weaknesses that exist in themselves, being sensitive to the surrounding environment, having a sense of empathy and compassion for God’s creation and will have peace of mind. The purpose of this research is to find out the effect of children’s yoga on pre-school children’s spiritual intelligence in Kebonromo village, Ngrampal sub-district, Sragen district. The design used in this research is Pre-Experimental with the One Group Pre-Post Test Design approach. The population of this study were pre-school children’s in Kebonromo village, Ngrampal sub-district, Sragen district. Sample of 10 pre-school children respondents. Spiritual intelligence questionnaire instruments and children’s yoga SOP. Data analysis used univariate and bivariate analysis. The bivariate test results show that the Zcount value of the Wilcoxon Signed Ranks Test is -2.825 with a significance value (p-value) of 0.005. The significance value of the test is less than 0.05 (0.005 < 0.05) so that the test decision is H0 rejected, which means there is a significant difference in spiritual intelligence scores between the pre test and post test. The conclusion is there is an effect of children’s yoga on pre-school children’s spiritual intelligence in Kebonromo village, Ngrampal sub-district, Sragen district. The suggestion from this research is that it is hoped that children will be able to carry out child yoga regularly to get the benefits of children’s yoga, especially to develop children’s spiritual intelligence. ABSTRAK Dalam mengoptimalkan kecerdasan spiritual diperlukan proses panjang serta memerlukan latihan, semakin dini anak dilatih untuk mengembangkan kecerdasan spiritual maka akan semakin besar manfaatnya antara lain anak mampu mengenali diri sendiri, mampu mengenali kelebihan dan kekurangan yang ada pada dirinya, peka terhadap lingkungan sekitar, memiliki rasa empati dan belas kasih terhadap ciptaan Tuhan serta akan memiliki ketenangan dalam berpikir. Salah satu cara untuk meningkatkan kecerdasan spiritual dengan melakukan yoga. Tujuan penelitian ini adalah untuk mengetahui pengaruh yoga anak terhadap kecerdasan spiritual anak pra sekolah di Desa Kebonromo Kecamatan Ngrampal Kabupaten Sragen. Desain yang digunakan dalam penelitian ini adalah Pra Eksperimental dengan pendekatan One Group Pra-Post Test Design. Populasi dari penelitian ini adalah anak pra sekolah di Desa Kebonromo Kecamatan Ngrampal Kabupaten Sragen. Sampel 10 responden anak pra sekolah. Instrumen angket kecerdasan spiritual dan SOP yoga anak. Analisis data menggunakan Analisis Univariat dan bivariat. Hasil uji bivariat menunjukkan bahwa nilai Zhitung uji Wilcoxon Signed Ranks Test adalah sebesar -2,825 dengan nilai signifikansi (p-value) 0,005. Nilai signifikansi uji ternyata lebih kecil dari 0,05 (0,005 < 0,05) sehingga keputusan uji adalah H0 ditolak yang bermakna terdapat perbedaan yang signifikan skor kecerdasan spiritual antara pre test dan post test. Kesimpulannya adalah ada pengaruh yoga anak terhadap kecerdasan spiritual anak pra sekolah di Desa Kebonromo Kecamatan Ngrampal Kabupaten Sragen. Saran dari penelitian ini adalah diharapkan anak-anak mampu melaksanakan yoga anak ini secara rutin untuk mendapatkan manfaat dari yoga anak terutama untuk mengembangkan kecerdasan spiritual anak.